Printable Elastic Porous Conductor for Stretchable Keypads - Lee, Jongsu; Kim, Sun Hong; Cho, Duho; Chae, Changju; Jung, Sungmook (John Wiley & Sons Ltd., 2025)
Electrodes, which are essential components of electronic devices, must possess high electric conductivity; thus, most electronic devices currently use rigid metal electrodes. However, electrode stretchability is important for wearable applications, which have recently attracted significant attention. This study describes a strategy for fabricating printable and highly stretchable porous conductors by combining silver flakes with poly(3,4-ethylenedioxythiophene) polystyrene sulfonate. It is found that the fabricated electrode can be stretched by over 400% while retaining high conductivity, which decreases from 532.9 S center dot cm(-1) at 0% strain to 133.2 S center dot cm(-1). Furthermore, the novel electrodes exhibits high durability even after 1000 cycles of 100% stretching, which can be an ideal characteristic for skin electronics. The obtained conducting material is used as an electrode for a wearable keyboard, which can be rolled up/out repeatedly, and its reliability exceeds 1000 cycles of operation.